PHYTOCHEMICAL ANALYSIS AND IN VITRO ANTIINFLAMMATORY ACTIVITY OF PERGULARIA DAEMIA (Forsk.) - TAMIL SELVI I; VIDHYA R (Innovare Journal of Life Sciences, 2019)
Objectives: The in vitro antiinflammatory activity of acetone and ethyl acetate extracts of Pergularia deamia leaf and stem. Methods: The different parts of extracts were subjected to preliminary phytochemical screening as per the standard protocols. In vitro anti-inflammatory activities were evaluated by red blood cell (RBC) membrane stabilization, protein denaturation, and antiproteinase methods. Results: Preliminary phytochemical screening revealed that the presence of carbohydrates, phenol, tannins, flavonoids, alkaloids, steroids, and quinines in acetone extracts of plant. In vitro anti-inflammatory activities were tested using different concentrations of the extracts along with standard drug diclofenac sodium. The maximum anti-inflammatory activities were observed in ethyl acetate extracts of P. daemia. As the concentration of the extracts increased antiinflammatory activity also higher. Conclusion: The plant, therefore, might be considered as a natural source of RBC membrane stabilizers and prevention of protein denaturation, so it is substitute medicine for the management of inflammatory disorder.